The science in me: worktext in science - How, Giam Kah; How, Giam Kah (Manila, Philippines : Rex Book Store., 2019)
The Scientist in Me series is specially designed to cater to the needs of the pupils to understand the basic science concepts, to apply science inquiry skills, and to exhibit scientific attitudes and values.
Things Around Us--Ourselves--Animals--Plants--Our Environment--Force and Motion--Energy--Soil--Weather--Sky
English